I am reading a book about C*-algebra. When i study von Neumann algebras in this book, i meet with a problem. In the book,

If $H$ is a Hilbert space, we write $H^{(n)}$ for the orthogonal sum of n copies of $H$. If $a\in M_{n}(B(H))$ (an operator matrice), we define $\phi(a)\in B(H^{(n)})$ by setting $$\phi(a)(x_{1}, x_{2},..., x_{n})=(\Sigma_{j=1}^{n}a_{1j}(x_{j}),...,\Sigma_{j=1}^{n}a_{nj}(x_{j})),$$ for all $(x_{1}, ...,x_{n})\in H^{(n)}$. It is easy to verify that the map $$\phi: M_{n}(B(H)) \rightarrow B(H^{(n)}), a\rightarrow \phi(a),$$ is a *-isomorphism.

My question is how to verify that $\phi$ is a *-isomorphism. I suppose it is not an easy conclusion for me .

  • $\begingroup$ The first thing is to verify that it is a bijection (linearity should be clear), then check that $\phi(a^\ast) = \phi(a)^\ast$. $\endgroup$ – Daniel Fischer Nov 7 '13 at 15:52
  • $\begingroup$ I know that, but how? $\endgroup$ – Yan kai Nov 7 '13 at 16:02
  • $\begingroup$ What part have you problems with? Bijectivity is most easily proved by giving the inverse. The $^\ast$ property is a direct verification. $\endgroup$ – Daniel Fischer Nov 7 '13 at 16:04
  • $\begingroup$ I do not know what is the specific form of $\phi(a)^{*}$. $\endgroup$ – Yan kai Nov 7 '13 at 16:10
  • $\begingroup$ Well, you have $\langle \phi(a)v,w\rangle = \langle v, \phi(a)^\ast w\rangle$ for all $v,w\in H^{(n)}$. And that's the defining identity, so show $\langle \phi(a)v,w\rangle = \langle v,\phi(a^\ast)w\rangle$ for all $v,w \in H^{(n)}$. $\endgroup$ – Daniel Fischer Nov 7 '13 at 16:17

I will use the notation $$ (x_1,\ldots,x_n)=\bigoplus_{k=1}^nx_k. $$ So $$ \left\langle\bigoplus_{k=1}^nx_k,\bigoplus_{k=1}^ny_k\right\rangle=\sum_{k=1}^n\langle x_k,y_k\rangle. $$

With the same proof as for complex matrices, one shows that $\phi(a)^*=\phi(a^*)$, where $(a^*)_{kj}=a_{jk}^*$: $$ \langle\phi(a)\bigoplus_{k=1}^nx_k,\bigoplus_{k=1}^ny_k\rangle=\langle\bigoplus_{k=1}^n\sum_{j=1}^na_{kj}x_j,\bigoplus_{k=1}^ny_k\rangle=\sum_{k=1}^n\sum_{j=1}^n\langle a_{kj}x_j,y_k\rangle =\sum_{j=1}^n\sum_{k=1}^n\langle x_j,a_{kj}^*y_k\rangle=\sum_{j=1}^n\langle x_j,\sum_{k=1}^na_{kj}^*y_k\rangle=\langle\bigoplus_{j=1}^nx_j,\bigoplus_{j=1}^n\sum_{k=1}^na_{kj}^*y_k\rangle=\langle\bigoplus_{j=1}^nx_j,\phi(a^*)\bigoplus_{j=1}^ny_j\rangle =\langle\phi(a^*)^*\bigoplus_{k=1}^nx_k,\bigoplus_{k=1}^ny_k\rangle. $$ So $\phi(a^*)^*=\phi(a)$ for all $a$, which implies that $\phi(a^*)=\phi(a)^*$.

We have $$ \phi(a+b)(\bigoplus_{k=1}^nx_k)=\bigoplus_{k=1}^n\sum_{j=1}^n(a+b)_{kj}x_j=\bigoplus_{k=1}^n\sum_{j=1}^n\,a_{kj}x_j+b_{kj}x_j\\=\bigoplus_{k=1}^n\sum_{j=1}^n\,a_{kj}x_j+\bigoplus_{k=1}^n\sum_{j=1}^n\,b_{kj}x_j=\phi(a)(\bigoplus_{k=1}^nx_k)+\phi(b)(\bigoplus_{k=1}^nx_k)=[\phi(a)+\phi(b)]\bigoplus_{k=1}^nx_k, $$ showing that $\phi$ is linear. Also, $$ \phi(ab)(\bigoplus_{k=1}^nx_k)=\bigoplus_{k=1}^n\sum_{j=1}^n(ab)_{kj}x_j=\bigoplus_{k=1}^n\sum_{j=1}^n\sum_{h=1}^na_{kh}b_{hj}x_j=\bigoplus_{k=1}^n\sum_{h=1}^na_{kh}\sum_{j=1}^nb_{hj}x_j =\phi(a)(\bigoplus_{k=1}^n\sum_{j=1}^nb_{hj}x_j)=\phi(a)\phi(b)(\bigoplus_{k=1}^nx_k), $$ and then $\phi(ab)=\phi(a)\phi(b)$.

If $\phi(a)=0$, then $\sum_{j=1}^na_{kj}x_j=0$ for any $k$ and any $x_1,\ldots,x_n$. From here we can see that $a_{kj}=0$ for all $k,j$. That is, $a=0$. So $\phi$ is injective.

Finally, let $T\in B(H^{(n)})$. Let $\pi_j$ be the map $\displaystyle\bigoplus_{k=1}^nx_k\mapsto x_j$. Then define $T_{kj}\in B(H)$ by $$ T_{kj}x=\pi_k T(0,\ldots,0,x,0,\ldots,0), $$ where the $x$ is in the $j^{\rm th}$ place in the $n$-tuple. Then $$ \phi((T_{kj})_{kj})(\bigoplus_{k=1}^nx_k)=\bigoplus_{k=1}^n\sum_{j=1}^nT_{kj}x_j=\sum_{j=1}^n\bigoplus_{k=1}^nT_{kj}x_j=\sum_{j=1}^n\bigoplus_{k=1}^n\pi_kT(0,\ldots,0,x_j,0,\ldots,0)\bigoplus_{k=1}^n\pi_kT(\bigoplus_{k=1}^nx_j)=T(\bigoplus_{k=1}^nx_k). $$ And so $\phi$ is surjective.

  • $\begingroup$ (+1) though that was a very simple question, you put a lot of efforts $\endgroup$ – Norbert Nov 7 '13 at 18:37
  • $\begingroup$ Thanks. I try to answer with the mentality that answers should be useful to others in the future. $\endgroup$ – Martin Argerami Nov 8 '13 at 1:51
  • $\begingroup$ Thanks for your detailed answer, Martin Argerami. :) $\endgroup$ – Yan kai Nov 8 '13 at 1:58

I answered a similar question previously, you may (or may not) find this helpful A theorem about operators in Hilbert sapce.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.